2003
DOI: 10.1007/s00213-003-1658-9
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone augmentation of neuroleptic treatment in alcohol abusing patients with schizophrenia

Abstract: These data suggest that naltrexone may be an effective medication for individuals with comorbid alcohol dependence and schizophrenia. Given the widespread problems associated with alcohol misuse in this population, and the lack of effective pharmacotherapies, these findings represent an exciting clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 42 publications
2
52
0
2
Order By: Relevance
“…However, data suggesting that naltrexone may have value in this population [42] may indicate that blocking the rewarding effect of alcohol (without decreasing overall hedonic tone, as could occur during treatment with a potent D2 blocking agent, such as haloperidol [106], also could facilitate effective treatment in some patients. However, by contrast, the potential value of disulfiram, which provides a negative reinforcement to alcohol use, seems to decrease alcohol use in a manner akin to that for psychosocial interventions described below.…”
Section: Pharmacologic Treatmentsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, data suggesting that naltrexone may have value in this population [42] may indicate that blocking the rewarding effect of alcohol (without decreasing overall hedonic tone, as could occur during treatment with a potent D2 blocking agent, such as haloperidol [106], also could facilitate effective treatment in some patients. However, by contrast, the potential value of disulfiram, which provides a negative reinforcement to alcohol use, seems to decrease alcohol use in a manner akin to that for psychosocial interventions described below.…”
Section: Pharmacologic Treatmentsmentioning
confidence: 94%
“…Naltrexone, an agent that has been shown to reduce alcohol consumption in people with primary alcohol use disorders, also may be associated with decreased use and craving for alcohol in patients with comorbid SUDs and schizophrenia or bipolar disorder [42]. The one randomized placebocontrolled study of naltrexone plus cognitive behavioral therapy (CBT) for patients with schizophrenia and alcohol use disorders reported that, compared with patients receiving placebo and CBT, patients receiving naltrexone and CBT had more days of abstinence and less alcohol craving [42].…”
Section: Other Medications To Treat Substance Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Naltrexone decreased alcohol use and improved depressive symptoms in an open study with patients manifesting alcohol dependence (Salloum et al, 1998). A small, placebo-controlled, randomized clinical trial with naltrexone in 31 patients manifesting schizophrenia and alcohol dependence (Petrakis et al, 2004) showed naltrexone-treated patients had fewer drinking days and "heavy drinking" days and less "craving" in comparison to patients treated with placebo. Overall, naltrexone was well tolerated and did not cause a worsening of psychosis.…”
Section: Pharmacotherapy Of Alcohol Use Disorders 2009mentioning
confidence: 98%
“…Many studies indicate that treatment of SUD among psychiatric patients is associated with better drug-related, psychiatric and psychosocial outcomes (e.g. [9,10,11,12,13,14,15,16]). Considering this, identification of SUD among psychiatric patients is of importance.…”
Section: Introductionmentioning
confidence: 99%